THE CORRELATION BETWEEN SELF CONFIDENCE AND ENGLISH SPEAKING SKILL OF THE EIGHTH-GRADE STUDENTS OF SMPN 1 BLAHBATUH - Ni Wayan Ema Parmita (Academic Journal on English Studies (AJOES), 2022)
The present study dealt at finding out the correlation between self-confidence and English speaking skill of the eighth grade students of SMPN 1 Blahbatuh in academic year 2021/2022, the variables of this study were students’ self-confidence and English speaking skill. Which were self-confidence as variable X and English speaking skill as variable Y. Population were the eighth grade students of SMPN 1 Blahbatuh in academic year 2021/2022. There are students that were selected as the sample of the study which chosen in one class. The researcher takes sample 10% of population which taken 40 samples. The data collected in this research was analyzed by using Pearson Product Moment Correlation in SPSS Statistics 25. According to the results of the data statistical calculation, it was found .321. It shows that there is significant correlation between self-confidence and English speaking skill of the eighth grade students of SMPN 1 Blahbatuh in academic year 2021/2022. Based on the result, it was shown that .321 was in interval low correlation between self-confidence and English speaking skill.